Neutral density estimation derived from meteoroid measurements using high‐power, large‐aperture radar. Issue 13 (4th July 2016) - Li, A.; Close, S.
Abstract: We present a new method to estimate the neutral density of the lower thermosphere/upper mesosphere given deceleration measurements from meteoroids as they enter Earth's atmosphere. By tracking the plasma (referred to as head echoes) surrounding the ablating meteoroid, we are able to measure the range and velocity of the meteoroid in 3‐D. This is accomplished at Advanced Research Projects Agency Long‐Range Tracking and Instrumentation Radar (ALTAIR) with the use of four additional receiving horns. Combined with the momentum and ablation equations, we can feed large quantities of data into a minimization function which estimates the associated constants related to the ablation process and, more importantly, the density ratios between successive layers of the atmosphere. Furthermore, if we take statistics of the masses and bulk densities of the meteoroids, we can calculate the neutral densities and its associated error by the ratio distribution on the minimum error statistic. A standard deviation of approximately 10% can be achieved, neglecting measurement error from the radar. Errors in velocity and deceleration compound this uncertainty, which in the best case amounts to an additional 4% error. The accuracy can be further improved if we take increasing amounts of measurements, limited only by the quality of the ranging measurements and the probability of knowing the median of the distribution. Data analyzed consist mainly of approximately 500 meteoroids over a span of 20 min on two separate days. The results are compared to the existing atmospheric model NRLMSISE‐00, which predicts lower density ratios and static neutral densities at these altitudes. Key Points: Detection of meteor head echoes through HPLA radars Minimization of ablation equations to calculate neutral densities and ablation parameters Error roughly 10%–12% across binned estimates